Short-Term Outcome Among Full-Term Neonates with Moderate/Severe Hypoxic-Ischemic Encephalopathy Admitted in Neonatal Intensive Care Unit in A Tertiary Care Hospital in Rawalpindi - Malik, Hina Zafar; Mahmood, Menahyl; Samreen, Khalida (Biological and Clinical Sciences Research Journal, 2025)
Hypoxic-ischemic encephalopathy (HIE) is a major contributor to neonatal morbidity and mortality, particularly in low- and middle-income countries. Objective: To determine the short-term clinical outcomes among full-term neonates with moderate to severe HIE admitted to the Neonatal Intensive Care Unit (NICU) of a tertiary care hospital. Methods: This cross-sectional study was conducted over six months from October 2024 to March 2025. at the Department of Paediatrics and Child Health, Benazir Bhutto Hospital, Rawalpindi. A total of 155 full-term neonates diagnosed with moderate or severe HIE were enrolled using convenience sampling. Data were collected through clinical assessments and medical records using a structured proforma. Results: Among 155 neonates, 57.4% had moderate HIE and 42.6% had severe HIE. Overall mortality was 14.2%, significantly higher in severe HIE cases (27.3%) compared to moderate (4.5%) (p<0.001). Mechanical ventilation was required in 38.1% of neonates, more frequently in severe HIE (62.1%) than moderate (20.2%) (p<0.001). Seizures occurred in 29.7% of cases, significantly higher in the severe group (48.5%) versus moderate (15.7%) (p<0.001). PPV was needed in 72.3% of cases, with no significant difference between groups. Apgar score ≤4 and birth weight <2.5 kg were associated with significantly poorer outcomes. Conclusion: It is concluded that severity of HIE is directly associated with adverse short-term outcomes, including mortality, mechanical ventilation, and seizure occurrence. Early identification of high-risk neonates through Apgar scores and birth weight assessment, alongside appropriate NICU support, is essential for improving neonatal prognosis in resource-limited settings.